Academic design/build programs as mechanisms for community development - Rice-Woytowick, Pamela A. (Kansas State University, 2011)
Academic design/build programs can serve as vehicles for community development. As design professionals working within the community context, architects hold the potential to create community betterment and build community assets through their work, although this focus does not appear to be central to the culture of American architecture. In particular, a review of architecture curricula in the United States reveals the lack of design/build opportunities for students. Design/build programs integrated in academic architectural programs have been in existence for just about two decades. As such, development of their pedagogy and organizational structure is emerging. It is timely to identify the common and distinguishing factors of established design/build efforts in architecture schools and to examine the role community development plays in each. Established academic design/build programs were identified for further study, enabling identification of commonalities within the structural frameworks of programs as well as contextual nuances; the identification of programs which purposely instigate community development; and the identification of the factors within those programs which act as mechanisms for community development. The result is a framework for organizing a community development initiative which is central to the architectural process and to design/build pedagogy.
Keywords: Architecture; Community Development; Architecture (0729)